2012
DOI: 10.1128/jvi.06097-11
|View full text |Cite
|
Sign up to set email alerts
|

Significant Association of Multiple Human Cytomegalovirus Genomic Loci with Glioblastoma Multiforme Samples

Abstract: Viruses are appreciated as etiological agents of certain human tumors, but the number of different cancer types induced or exacerbated by viral infections is unknown. Glioblastoma multiforme (GBM)/astrocytoma grade IV is a malignant and lethal brain cancer of unknown origin. Over the past decade, several studies have searched for the presence of a prominent herpesvirus, human cytomegalovirus (HCMV), in GBM samples. While some have detected HCMV DNA, RNA, and proteins in GBM tissues, others have not. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
115
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 38 publications
3
115
0
5
Order By: Relevance
“…26 Other studies have suggested that halted differentiation of neuroprogenitor cells is an early step in gliomagenesis. 27 Since HCMV proteins and nucleotide sequences seem to be present in most GBMs 16,[28][29][30] and that HCMV-IE expression is a prognostic marker for poor patient survival irrespective of the GBM subtype, 18 our present model of HCMV infection of primary GBM cells appears to recapitulate early events during glioma development.…”
Section: Discussionmentioning
confidence: 90%
“…26 Other studies have suggested that halted differentiation of neuroprogenitor cells is an early step in gliomagenesis. 27 Since HCMV proteins and nucleotide sequences seem to be present in most GBMs 16,[28][29][30] and that HCMV-IE expression is a prognostic marker for poor patient survival irrespective of the GBM subtype, 18 our present model of HCMV infection of primary GBM cells appears to recapitulate early events during glioma development.…”
Section: Discussionmentioning
confidence: 90%
“…25 Recently, another study using 12 primer pairs and semi-QPCR also revealed the significantly higher incidence of CMV-DNA in a proportion of glioblastoma samples compared with non-tumor tissues. 26 One reason for this discrepancy may be because extremely small amount of DNA can be detected by traditional PCR techniques that were utilized such as nested-PCR utilized in the previous study 1 in which 35-50 cycles of amplification followed by a second round of amplification, and HCMV DNA from cells other than the tumor cells were detected. Glioblastoma is often accompanied with reactive gliosis at the edge of the tumor tissue, and microglial cells that originate from bone marrow myeloid cells, which may be persistently infected by HCMV, 27 could have important roles in the development of gliosis.…”
Section: Discussionmentioning
confidence: 93%
“…With current standard therapy, median overall survival (OS) for GBM patients is less than 15 mo after diagnosis. 1,2 An active HCMV infection, as determined by HCMV protein expression, can be detected in tumor cells in 90-100% of GBM patients; [3][4][5][6][7][8] however, the infection is absent in healthy surrounding tissues, indicating a potential oncomodulatory or oncogenic role of HCMV. We found that the median OS of GBM patients correlates with the grade of HCMV infection in tumor tissue.…”
mentioning
confidence: 99%